2019
DOI: 10.1136/bmjopen-2019-031339
|View full text |Cite
|
Sign up to set email alerts
|

Effects of a probiotic treatment (Enterococcus faecalis) and open-label placebo on symptoms of allergic rhinitis: study protocol for a randomised controlled trial

Abstract: IntroductionSeveral studies suggest that gut microbiota may play an important role in allergic diseases. The present trial aims to examine effects of the probiotic Enterococcus faecalis on symptoms of allergic rhinitis in patients. Effects of this probiotic on the immune system have been reported by several studies, but the majority of the previous trials were animal studies. In addition, it is well known that symptoms in allergic rhinitis are prone to exhibit high placebo responses. Moreover, recent studies r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 68 publications
0
13
0
Order By: Relevance
“…Finally, open label placebo treatment ( 84 ) can be added to a conventional placebo-controlled trial, either with full double-blinded randomization ( 85 ) or allowing patient preferences for either arm, what has been called preference design ( 19 ).…”
Section: Resultsmentioning
confidence: 99%
“…Finally, open label placebo treatment ( 84 ) can be added to a conventional placebo-controlled trial, either with full double-blinded randomization ( 85 ) or allowing patient preferences for either arm, what has been called preference design ( 19 ).…”
Section: Resultsmentioning
confidence: 99%
“… 4 , 5 Previous studies have confirmed that the microbiome directly affects inflammatory responses in allergic diseases such as AR and asthma. 6 , 7 , 8 Therefore, the study of the composition of the microbiota is of great importance for understanding the pathogenesis of AR.…”
Section: Introductionmentioning
confidence: 99%
“…To circumvent these challenges, open-label placebo (OLP) interventions administer placebos in an unconcealed fashion with the individual’s awareness and consent. Encouraging pioneering studies suggest beneficial effects of OLP in different clinical conditions, e. g., cancer-related fatigue 16 , chronic back pain 17 , 18 , allergic rhinitis 19 , attention deficit hyperactivity disorder 20 or irritable bowel syndrome 21 . A first meta-analysis of these initial studies confirms these effects 22 .…”
Section: Introductionmentioning
confidence: 99%